Superb pseudocapacitance observed from eco-friendly multi-dimensional quaternary composite electrode based on Ce and Cu oxides and sulfides. Issue 8 (1st June 2019) - Kim, Seong Ku; Pukird, Supakorn; Chaiyo, Pitchanunt; Inchidjui, Pakin; Bae, Garam; Jung, Ha-Kyun; Lee, Sun Sook; An, Ki-Seok
Abstract: A multi-dimensional environmentally friendly quaternary composite electrode for pseudocapacitors is synthesized through a simple one-step hydrothermal method. The quaternary composite electrode consists of cerium oxide, cerium sulfides (Ce2 S3 and CeS2 ), and cuprous oxide, all of which are based on non-toxic transition metal elements with good natural abundances. Investigation of the microstructures has revealed the formation of nanostructures of cerium oxide and cerium sulfides with high specific capacitances on relatively conductive cuprous oxide. Due to synergistic interaction between these oxides and sulfides, the quaternary electrode exhibits exceptionally high specific capacitances ranging up to 650 F g −1 . In addition, great cyclic stability is observed during 1000 cycles of repeated charging and discharging at a constant current of 10 A g −1 .